The Decision Support System Determines The Effectiveness Of The Pelita Nusantara Stmik Promotion Media With The Profile Matching Method - Ramli S. Siburian; Agustina Simangunsong (Jurnal Mandiri IT, 2022)
In carrying out promotional activities, the level of effectiveness of a promotional media used by the promotion team greatly influences the results to be achieved. Therefore, it is necessary to pay attention to which promotional media is more appropriate to use when conducting promotions. In decision making, the researcher uses the Profile Matching method. The Profile Matching method is used as a mechanism in decision making by assuming that there is an ideal level of predictor variables that must be met by the subject under study, not a minimum level that must be met or passed. In the Profile Matching process, a comparison process will be carried out between individual competencies into standard competencies, in this case the ideal Raskin profile, so that differences in competence can be known. From the decision-making process carried out will obtain the results of the most effective promotional media used in carrying out promotional activities.